Role of ortho-pantho-graphic X-ray in the diagnosis of osteoporosis - Nouh, Hassan M.; Alomami, Amina R. (International Journal of Research in Orthopaedics, 2024)
Background: Osteoporosis affects people, especially old age, as postmenopausal women and remains unnoticeable until the patient presents with a fracture. Osteoporosis in human begins started with the loss of bone mass that increases with age, this is related to the decrease in bone density and an increase in porosity that will cause fractures in this osteoporotic bone. Objective was to assess the usefulness of orthopanthographic (OPG) in the early detection of osteoporosis. Methods: This is an analytic across-sectional test validation study, was done in Hawari Hospital-Benghazi, Libya which considered a referral General Hospital affiliated with University of Benghazi. This study was done during a period from March 2022 to July 2023. Sixty women were selected, divided into osteoporotic and non osteoporotic groups depending on the clinical and laboratory investigations under the supervision of an orthopedic consultant in the outpatient clinic. Panoramic radiographic X-rays were taken for evaluation and estimation of the mandibular cortex on the basis of (Mental index, Klemetti index, and Panoramic mandibular index) as a diagnostic tool to differentiate normal from osteoporotic patient, all three indices correlated significantly with bone mineral density and used as useful indicators for detected the osteopenia and osteoporosis. Results: We calculated values of the three indices (Mental index, Klemetti index, and Panoramic mandibular index) values were low especially in the osteoporotic group, as well the values of mental index and panoramic mandibular index were low compared with low bone mineral density of the patient and klemetti index with: C2, C3 categories (moderate and severe erosion) most common observed in the osteoporotic patient. Conclusions: Orthopanthographic X-rays provide a valuable tool for early detection and assessment of osteoporosis (preclinical stage) especially when characterized by a decrease in bone mineral density.